Mexico - Income Generation and Social Protection for the Poor : Volume 1. Integrated Executive Summary - World Bank (Washington, DC, 2012)
This document summarizes the findings of three reports: Urban Poverty in Mexico, Mexico: a Study of Rural Poverty, and Mexico: an Overview of Social Protection, and, focuses on 1) the generation of income opportunities for the urban and rural poor, and, 2) social protection for the poor. The main messages can be summarized as follows. The poor are a heterogeneous group; importantly, long-term income-generating opportunities and coping strategies differ significantly between urban and rural areas, among different regions, between small and larger cities, and even within neighborhoods. This translates into having urban poor limited to low-quality jobs, marked by low productivity and with limited social protection. Additionally, to continue supporting the rural poor move out of poverty, it is important to increase agricultural productivity, especially for small- and medium-sized farmers, and facilitate their diversification into rural non-farm activities (RNF) of higher agricultural value-added. The rural poor depend mainly on self-subsistence agriculture, self-employment, and non-agricultural activities, and have typically not completed primary education. Conversely, the urban poor depend on access to salaried employment, on non-agricultural activities, mainly as employees in manufacturing or services, and have not completed lower secondary education. Since its inception in the 1940s, Mexico's social protection system has not been well-suited to respond to the risks the poor face. A key conclusion of this report is that geographical location must be taken into account, in order to design adequate poverty interventions - income generation opportunities and social protection needs vary depending upon the poor's location.